The Role of Digital Technology in Sustaining Online Learning during the Pandemic Covid19 - Muhammad Nang Al Kodri (UICELL, 2020)
In the midst of the Covid19 pandemic, a rule emerged, especially in Indonesia, where Indonesians are required to maintain a minimum distance from one another to one so that Indonesians are forced to stay at home and do all activities from home such as working from home, and learning from home. With the existence of rules for activities from home such as working from home, studying from home, these activities require the role of technology to carry out these activities. The role of technology digital during the Covid19 periods was very large, for example, like learning from home; this learning was carried out via DARING or in a network by utilizing an application or web which is commonly known as e-learning. E-learning is a distance learning process by combining the principles in the learning process with technology. Digital technology plays an important role in overcoming the problems of the learning process carried out online. Even though it is not as effective as possible with face to face learning in the presence of sophisticated technology, nowadays it is quite helpful in the online-based learning process. However, the role of technology is very sophisticated does not run better without the creativity of a teacher in learning.